Should I provide my health data for research? Citizens assessing the value of data provision - Susanne Oechsner; Robin Rae; Ulrike Felt (Big Data & Society)
In March 2024, the European Parliament and Council agreed to implement the European Health Data Space (EHDS), the first domain-specific common EU data space. Next to improving healthcare delivery in national and cross-border settings, the EHDS aims to advance the reuse of health data in research, innovation, policy-making, and personalized medicine. However, to fully harness the potential of a data-driven approach to health research and care, citizens must be willing to provide their data for research. To understand the conditions under which citizens are prepared to do so, this article investigates the situated ways in which they reflect on and assess their (non)provision of digitally available health data for research. Our empirical work is situated within a large-scale EU-funded project that sought to develop a health data infrastructure for transborder healthcare and research. Using a diverse set of engagement methods, we investigated how citizens value the provision of their health (care) data for secondary use in research and examined the valuation constellations that shape their assessments. Our analysis shows that citizens’ valuations of a digital health infrastructure are by no means binary—defining it as either worth supporting or not—and that visions, positions, and decisions cannot be considered stable over time. Their willingness to share health data is shaped by dynamic evaluations grounded in mediated reciprocity, assessments of future data-use-related uncertainties, and the need for relational transparency. Realizing and maintaining the value of health data infrastructures thus requires continuous efforts, which must be reflected in both their material design and governance.